Treatment method of firework and firecracker production tailings
By using composite nanomaterials to treat fireworks and firecrackers to produce tailslags, the problems of burning and safety risks of tailslags are solved, and the safe treatment of tailslags and resource recycling are achieved.
Patent Information
- Application Number
- CN202411856486.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Fireworks and firecrackers production tails are highly flammable and explosive. Traditional treatment methods such as deep pit landfill and safe incineration have problems such as environmental pollution, safety hazards and explosion risks.
Compound nanomaterials, including nano zero-valent iron, activated carbon, sodium carboxymethylcellulose and propylene glycol, are used to treat tailings by stirring reaction and standing, to eliminate their ignition and explosive properties and achieve safe treatment.
Effectively eliminate the ignition and explosion of tailings, reduce safety risks, and meet strict environmental protection requirements. The treated tailings can be comprehensively recycled and utilized.
Smart Images

Figure CN119657617A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tailings treatment, in particular to a method for treating tailings from fireworks and firecrackers production. Background Art
[0002] During the production process of fireworks and firecrackers, due to safety requirements, the ground of the production plant and key parts of the charging system need to be sprayed with water to prevent the residual gunpowder powder from spontaneous combustion and explosion. In this process, a large amount of tailings enter the water treatment system with water. In traditional processes, these tailings are mainly treated by deep pit landfill or safe incineration. However, with the improvement of environmental protection requirements, deep pit landfill has been banned in many areas because it is easy to pollute soil and groundwater. Although safe incineration is a treatment method, it has extremely high requirements and there are major safety hazards. Most companies are resistant to this treatment method.
[0003] In addition, the tailings are still highly flammable and explosive after filtration, and there are huge safety risks whether they are transported and disposed of or stored in the factory. Therefore, how to effectively eliminate the flammability and explosion of tailings has become a key issue that needs to be urgently solved in the fireworks industry. Existing problems: Environmental pollution: Traditional landfill methods are prone to soil and groundwater pollution. Safety hazards: Safe incineration requires high requirements, there are safety hazards, and companies are generally reluctant to adopt it. Explosion risk: Tailings are highly flammable and explosive, which increases the safety risks of transportation and storage. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for treating tailings from the production of fireworks and firecrackers. Composite nanomaterials are used to eliminate the flammability and explosion of tailings from fireworks and firecrackers, thereby achieving safe treatment of tailings to meet increasingly stringent environmental protection requirements and reduce safety risks.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for processing tailings from fireworks and firecrackers production, comprising the following steps:
[0007] 1) separating the tailings from fireworks and firecrackers production into solid and liquid to obtain tailings material;
[0008] 2) mixing the tailings obtained in step 1) with the composite nanomaterial, and then stirring and reacting and standing to obtain a standing material;
[0009] The mass ratio of the tailings material to the composite nanomaterial is 100:1;
[0010] The stirring reaction conditions include: a rotation speed of more than 150 rpm and a time of 2 to 4 hours;
[0011] The standing time is more than 8 hours;
[0012] The components of the composite nano material include nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol;
[0013] The mass ratio of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol is 10:34:4:1;
[0014] 3) Mixing the static material obtained in step 2) with water and filtering to obtain filter press tailings.
[0015] Preferably, the water content of the tailings material in step 1) is 75-85%.
[0016] Preferably, the preparation method of the composite nanomaterial in step 2) comprises: firstly dissolving the sodium carboxymethyl cellulose and propylene glycol respectively, then adding the nano zero-valent iron material and stirring continuously and evenly, and finally adding activated carbon and stirring continuously and mixing thoroughly and evenly.
[0017] Preferably, the volume ratio of the standing material to water in step 3) is 1:1.
[0018] Preferably, the pressure time of the filter press in step 3) is not less than 1 hour.
[0019] Preferably, the composite nanomaterial in step 2) further contains water, and the mass ratio of the total mass of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol to water is 10-15:85-90.
[0020] The composite nanomaterial of the present invention is composed of nano zero-valent iron, activated carbon powder, sodium carboxymethyl cellulose and propylene glycol in a specific ratio. The material uses its unique large surface area and strong activity characteristics to stabilize (mineralize) harmful elements in waste residues, effectively eliminate the flammability and explosion of tailings, and achieve safe treatment. The treated tailings can be transported to a professional disposal agency for secondary comprehensive recycling, thereby solving the environmental pollution and safety risk problems caused by traditional treatment methods.
[0021] The composite nanomaterial used in this method is composed of nano zero-valent iron, activated carbon powder, sodium carboxymethyl cellulose and propylene glycol in a ratio of 10:34:4:1. Processing process: First, the slag and water are separated by a spiral stacking machine. At this time, the water content in the solid slag accounts for about 75-85%. The slag after filtration is stirred and mixed with a composite nanomaterial. Through the unique large surface area and strong activity characteristics of the nanomaterial, the stabilization (mineralization) of harmful elements in the waste slag is achieved. The treatment time is not less than 2 hours. After treatment, the solid-liquid separation is carried out by a plate and frame filter press to ensure that the water content in the solid does not exceed 30%. The flammability and explosion of the tailings after treatment is eliminated, and the tailings can be transported to a professional disposal agency for secondary comprehensive recycling. Thereby achieving safe treatment of the tailings.
[0022] Basic principles of processing:
[0023] (1) Catalytic degradation of perchlorate ions
[0024] Nano-zero-valent iron has high active sites and can release a large number of free electrons autonomously. - , destroying the stable structure of perchlorate, achieving step-by-step degradation of perchlorate, and finally converting it into harmless chloride ions. The reaction is shown in formula (1-4).
[0025] ClO4 - +2H + +2e - =ClO3 - +2H2O (1)
[0026] ClO3 - +2H + +2e - =ClO2 - +2H2O (2)
[0027] ClO2 - +2H + +2e - =ClO - +2H2O (3)
[0028] C1O - +2H + +2e - =Cl - +2H2O (4)
[0029] (2) Stabilization of nitrate and sulfide ions
[0030] The material reacts with the waste residue to remove nitrate, sulfide and carbonate ions, and converts them into nitrogen, iron sulfide ore and iron carbonate ore, etc. The reaction is shown in formulas (5-7).
[0031] 2Fe+3CO3 2- =Fe2(CO3) 3(s) +6e - (5)
[0032] Fe+S 2- =FeS (s) +2e - (6)
[0033] 2NO3 - +12H + +10e - =N 2(g) +6H2O (7)
[0034] (3) Reduction and adsorption of heavy metals
[0035] In order to obtain brilliant and colorful effects, fireworks and firecrackers are added with various types of metal oxides, which causes their waste residues to have strong leaching toxicity.
[0036] As a strong reducing adsorbent, the composite nanomaterial can reduce heavy metal ions to insoluble or low-toxic forms, such as Cu(II) can be reduced to Cu (0) Or Cu2O. At the same time, the unique high specific surface area of nano zero-valent iron materials provides them with abundant adsorption sites, which can physically adsorb heavy metal ions, thereby achieving stable mineralization of heavy metal elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0038] Figure 1 The results of the flammability and explosion of the tailings from fireworks and firecrackers production in Example 1 before and after treatment;
[0039] Figure 2 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0040] Figure 3 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0041] Figure 4 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0042] Figure 5 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0043] Figure 6 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0044] Figure 7 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0045] Figure 8 This is a graph showing the results of the tailings inspection report after treatment in Example 1;
[0046] Fig. 9 This is the result diagram of the inspection report of the treated tailings of Example 1. DETAILED DESCRIPTION
[0047] The present invention provides a method for processing tailings from fireworks and firecrackers production, comprising the following steps:
[0048] 1) separating the tailings from fireworks and firecrackers production into solid and liquid to obtain tailings material;
[0049] 2) mixing the tailings obtained in step 1) with the composite nanomaterial, stirring and reacting the mixture, and standing the mixture to obtain a standing material;
[0050] The mass ratio of the tailings material to the composite nanomaterial is 100:1;
[0051] The stirring reaction conditions include: a rotation speed of more than 150 rpm and a time of 2 to 4 hours;
[0052] The standing time is more than 8 hours;
[0053] The components of the composite nano material include nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol;
[0054] The mass ratio of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol is 10:34:4:1;
[0055] 3) Mixing the static material obtained in step 2) with water and filtering to obtain filter press tailings.
[0056] The present invention separates the tailings from the production of fireworks and firecrackers into solid and liquid to obtain tailings material. The present invention does not specifically limit the source of the tailings from the production of fireworks and firecrackers. The present invention does not specifically limit the solid-liquid separation method, and those skilled in the art can use conventional methods. In the present invention, the water content of the tailings material is preferably 75-85%.
[0057] The present invention mixes the obtained tailings material with the composite nanomaterial, and then stirs and reacts and stands in sequence to obtain a standing material; the components of the composite nanomaterial are nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol; the mass ratio of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol is 10:34:4:1. In the present invention, the role of the nano zero-valent iron is to catalyze the degradation of perchlorate, nitrate, sulfide, and solidify heavy metals, the role of the activated carbon is to play the role of dispersing nano iron, and at the same time adsorb and aggregate harmful substances in the waste residue to improve the treatment efficiency of nano iron, the role of the sodium carboxymethyl cellulose is to prevent the agglomeration of nano materials as a dispersant, and the role of the propylene glycol is to prevent the agglomeration of nano materials as a dispersant, and reduce the oxidation of nano iron. In the present invention, the preparation method of the composite nanomaterial preferably includes: first dissolving the sodium carboxymethyl cellulose and propylene glycol separately, then adding the nano zero-valent iron material, and stirring evenly, and finally adding the activated carbon, stirring continuously, and mixing evenly. In the present invention, the mass ratio of the tailings to the composite nanomaterial is preferably 100:1. In the present invention, the stirring reaction conditions preferably include: a rotation speed of more than 150 rpm and a time of 2 to 4 hours. In the present invention, the standing time is preferably more than 8 hours. In the present invention, the composite nanomaterial also preferably contains water, and the mass ratio of the total mass of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol to water is 10 to 15:85 to 90.
[0058] The present invention mixes the obtained static material with water and performs filter pressing to obtain filter pressing tailings. In the present invention, the volume ratio of the static material to water is preferably 1: 1. In the present invention, the pressure time of the filter pressing is preferably not less than 1 hour.
[0059] The obtained filter press tailings can be recycled for comprehensive resource utilization, such as in the following two ways, but not limited to these:
[0060] (1) The enterprise adds yellow mud at a mass ratio of 20 to 40:1, stirs the ingredients and prepares the base mud for use in filling fireworks and firecrackers.
[0061] (2) It is transported to equipment with pyrometallurgy and mixed with coal at a mass percentage of 5-10% to be used as an ignition agent for coal.
[0062] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0063] Example 1
[0064] A method for processing tailings from fireworks and firecrackers production, comprising the following steps:
[0065] (1) First, a screw stacker is used to separate the solid and liquid of the wastewater in the sedimentation tank. After treatment, the wastewater returns to the sedimentation tank, and the tailings are transferred to the tailings treatment tank. At this time, the water content of the tailings is 75%;
[0066] (2) Add composite nanomaterials at a mass ratio of 1% and stir at a stirring rate of 150 rpm for 2 hours. After the reaction is completed, avoid more than 8 hours (processing every other day) to allow the tailings to react more fully and obtain the treated tailings;
[0067] The components of the composite nanomaterial are nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose, propylene glycol, and water. The mass ratio of nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose, and propylene glycol is 10:34:4:1; the mass ratio of the total mass of nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose, and propylene glycol to water is 13:87;
[0068] The preparation method of the composite nano material is as follows: firstly, the sodium carboxymethyl cellulose and propylene glycol are respectively dissolved in water, then the nano zero-valent iron material is added, and the mixture is continuously stirred to be uniform, and finally, the activated carbon is added, and the mixture is continuously stirred to be fully mixed;
[0069] (3) After treatment, tap water is added to the tailings at a volume ratio of 1:1, and after being fully mixed, it is pumped into a plate and frame filter press through a mud pump for filtration for 1.5 hours. The pressure time is not less than 1 hour, the pressure is 0.7 MPa, and the water content of the tailings after filtration is 28%.
[0070] The tailings after filtration were sent to the Hunan Provincial Fireworks and Firecrackers Product Safety Quality Supervision and Inspection Liling Authorized Station for inspection to see if they were combustible. Figure 1 The results show that it is not flammable and can be recycled for comprehensive resource utilization.
[0071] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for processing tailings from fireworks and firecrackers production, characterized in that: The following steps are involved: 1) separating the tailings from fireworks and firecrackers production into solid and liquid to obtain tailings material; 2) mixing the tailings obtained in step 1) with the composite nanomaterial, stirring and reacting the mixture, and standing the mixture to obtain a standing material; The mass ratio of the tailings material to the composite nanomaterial is 100:1; The stirring reaction conditions include: a rotation speed of more than 150 rpm and a time of 2 to 4 hours; The standing time is more than 8 hours; The components of the composite nano material include nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol; The mass ratio of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol is 10:34:4:1; 3) Mixing the static material obtained in step 2) with water and filtering to obtain filter press tailings.
2. The processing method according to claim 1, characterized in that: The water content of the tailings material in step 1) is 75-85%.
3. The processing method according to claim 1, characterized in that: The preparation method of the composite nanomaterial in step 2) comprises: firstly dissolving the sodium carboxymethyl cellulose and propylene glycol respectively, then adding the nano zero-valent iron material and stirring continuously and uniformly, and finally adding activated carbon and stirring continuously and mixing uniformly.
4. The processing method according to claim 1, characterized in that: The volume ratio of the standing material to water in step 3) is 1:
1.
5. The processing method according to claim 1, characterized in that: The pressure time of the filter press in step 3) is not less than 1 hour.
6. The processing method according to claim 1, characterized in that: The composite nano material in step 2) further contains water, and the mass ratio of the total mass of the nano zero-valent iron, activated carbon, sodium carboxymethyl cellulose and propylene glycol to water is 10-15:85-90.
Citation Information
Patent Citations
Method for removing heavy metals in hazardous waste incineration fly ash through nanometer zero-valent iron
CN105149317A
Preparation method of activated-carbon multi-point-location supported nano zero-valent iron composite material
CN107456967A
Method for improving stabilization efficiency of nanometer zero-valent iron in heavy metal composite polluted soil
CN108246794A
Method for repairing environmental hormone contaminated soil
CN110369482A
Modified nano zero-valent iron adsorbent as well as preparation method and application thereof
CN118767897A